KAJIAN KEBIJAKAN ANGGARAN DALAM RANGKA MENDUKUNG PEMBANGUNAN KETAHANAN PANGAN DI KABUPATEN LAMPUNG BARAT - Indra Gunawan; Drajat Martianto; Yayuk Farida Baliwati (Jurnal Gizi dan Pangan, 2008)
This research aims to analyze the local government budget policies in supporting food security dvelopment in Lampung Barat District. The design of this study is retrospective using seondary data from related institutions in Lampung Barat. To identify the share of credit and debit of local budget  or APBD, a Comparative Budget Statement (CBS) is used, and to identify the budget proportion for food security oriented programs/activities, the Content Analysis method is applied. From the CBS analysis result, it is revealed that the biggest share is from Dana Alokasi Umum (DAU) or General Alloctaion Fund, accounting for 66.25% and the smallest share is from Local Original Revenue or Pendapatan Asli Daerah (PAD), which is only around 1.60%. The share of Development Budget is approximately 57.58%, while the share of Routine Budget is 42.42%. It is also found that the Local Budget has increased constantly during the last 5 years with the average is Rp. 304 068 008 767.  From this amount, Rp24 286 406 768  or about 7.6% per annum has been allocated for food security development.